1981
DOI: 10.1007/bf00443240
|View full text |Cite
|
Sign up to set email alerts
|

Survival of microorganisms after drying and storage

Abstract: Bacteria, yeasts and fungi suspended in a dextran solution were added to ampoules containing strips of filter paper which were dried without vacuum conditions. The ampoules were sealed and stored in the dark at room temperature. Viability counts were made of the original suspension immediately after drying and after storage periods of 3-48 months. Although bacterial cultures of many general did not show much resistance against dry conditions, bacteria of 13 other general had survived well or moderately after 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…The survival rates of Arthrobacter, Pseudomonas, Mycobacterium, Escherichia, Micrococcus, and Saccharomyces cells were rather similar when the cells were counted immediately after fast or slow drying (20 min and 24 h, respectively). After prolonged storage, viabilities were higher for slow-dried, as opposed to fast-dried, cells (11,12). These observations were true for E. coli only when more than about 8 mg of water per 108 cells was present on paper filters.…”
Section: Hypertonicity and Hypotonicitymentioning
confidence: 98%
See 1 more Smart Citation
“…The survival rates of Arthrobacter, Pseudomonas, Mycobacterium, Escherichia, Micrococcus, and Saccharomyces cells were rather similar when the cells were counted immediately after fast or slow drying (20 min and 24 h, respectively). After prolonged storage, viabilities were higher for slow-dried, as opposed to fast-dried, cells (11,12). These observations were true for E. coli only when more than about 8 mg of water per 108 cells was present on paper filters.…”
Section: Hypertonicity and Hypotonicitymentioning
confidence: 98%
“…To dry cells in air, cultures may be applied to some inert support which can be held, until dry, under a vapor phase of controlled humidity or a stream of air. Immobilization of cells on dry sand or dry paper has been used to preserve the viability of beta-hemolytic streptococci and other bacteria for more than 4 years (12,213).…”
Section: Vol 58 1994mentioning
confidence: 99%
“…Dysfunction of intracellular enzymes has been proposed to be responsible for cell death at 83% RH. Antheunissen et al (2) showed that when dried slowly, rhizobia can survive desiccation for up to 4 years. These long-term storage studies are rare, but they show that in the family Rhizobiaceae, sinorhizobia can survive desiccation for years.…”
mentioning
confidence: 99%
“…Como se observó en este estudio, en lo referente a la preservación realizada en papel filtro, Antheunisse en 1981 encontró que esta técnica fue adecuada para 13 géneros de bacterias incluyendo E.coli, Pseudomonas y otras Enterobacterias, con una buena o moderada supervivencia (11).…”
Section: Discussionunclassified